Lasting legacies: Meeting the housing needs of Forgotten Australians from mid‐life to older age. Issue 2 (17th August 2021) - Coram, Veronica; Tually, Selina; Cornell, Victoria; Zufferey, Carole; Lovell, Fran
Abstract: "Forgotten Australians" are the estimated half a million children who were placed in institutional care in Australia from the 1920s to the 1980s. Increasing numbers are entering older age but many are poorly positioned to age well and with the supports they need. This is often because the lasting effects of childhood institutional care have contributed to poor housing outcomes, including housing insecurity, reliance on social housing, prevalence of rental stress and experiences of homelessness. This paper presents a review of the evidence on the housing experiences and outcomes of people who spent time in childhood institutional care. The evidence review was complemented by qualitative interviews with community service practitioners and representatives of advocacy groups. Based on the prior evidence and fieldwork, we identify data and service gaps that are likely to undermine the capacity of the housing and aged care sectors to improve the care and supports available for Forgotten Australians. We suggest potential improvements to service delivery for people who experienced institutional care as children and directions for further research. This paper contributes to a stronger evidence base around the housing and care needs of Forgotten Australians in mid‐ and later life.